An ecosystem approach to manage pelagic thresher shark (Alopias pelagicus) based in Kutaraja Ocean Fishing Port, Aceh - Inda Mardhatillah; Am Azbas Taurusman; Muhammad Fedi Alfiadi Sondita; Ilham Fajri; Muhammad Aris (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
Sharks is the dominant bycatch of purse seine and bottom longline vessels that landed in Kutaraja ocean fishing port, particularly pelagic thresher shark species (Alopias pelagicus). The management of shark fisheries in Aceh water is not well implemented. According to the IUCN red list, the pelagic thresher shark has been classified as an endangered species. The capture and trade of pelagic thresher sharks are regulated by CITES (Appendix II). So that Indonesia has to comply with the procedures of CITES due to it has been adopted through the Decree of Minister of Marine Affairs and Fisheries of the Republic of Indonesia Number 61/PERMEN-KP/2018. However, the exploitation and trading of the A. pelagicus continues and is not properly managed. It will threaten the extinction of the pelagic thresher shark population and in terms of a negative image of fisheries management in Indonesia, in particular. Thus, integrated management such as the ecosystem approach to fisheries management (EAFM) is needed to solve this problem. This study aims to evaluate the fisheries management status of the pelagic thresher shark based on EAFM indicator of fish resources domain, focusing in the Kutaraja ocean fishing port. This research was conducted by field measurement and interviews with key stakeholders. Data were analyzed using a multi-criteria analysis (MCA) approach through development of a composite index. The results showed that the trend of CPUE tends to fluctuate in the last 5 years. The total length of the sharks was relatively constant. The proportion of juvenile pelagic thresher sharks was 16% male, and 28% (female), and the shark was bycatch (1%) of the purse seine fishery, the fishing ground was getting further away and seemed to go close to the shark habitat. Based on this assessment, one could conclude that shark's fishery resources were in 'good' category, however, some indicators need to improve through better fisheries management actions.Keywords: EAFM; Alopias pelagicus; pelagic thresher shark; Kutaraja ocean fishing port